Pengaruh Migrasi Masuk, Tingkat Upah Minimum, dan Tingkat Inflasi terhadap Pengangguran Terbuka di Kota Pekanbaru - Indah Destari (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of in-migration, minimum wages, and inflation on the open poverty rate in Pekanbaru City for the period 2006–2024. The study uses a quantitative method with time series data sourced from the Central Statistics Agency (BPS) of Pekanbaru City. Data analysis was carried out using multiple linear regression. The results of the study indicate that partially in-migration has a positive and insignificant effect on the open poverty rate, minimum wages have a negative and significant effect, while inflation has a negative and insignificant effect. Simultaneously, in-migration, minimum wages, and inflation have a significant effect on the open poverty rate in Pekanbaru City. Among the variables in-migration, minimum wages and inflation. The minimum wage level variable has the most dominant effect on open poverty in Pekanbaru City. The Adjusted R-Squared value of 0.6989 indicates that 69% of the variation in the open unemployment rate can be explained by the variables in the study, while the rest is influenced by other factors outside the research model.